2014
DOI: 10.1177/1740774514540814
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating protocol lifecycle time intervals in HIV/AIDS clinical trials

Abstract: Background Identifying efficacious interventions for the prevention and treatment of human diseases depends on the efficient development and implementation of controlled clinical trials. Essential to reducing the time and burden of completing the clinical trial lifecycle is determining which aspects take the longest, delay other stages, and may lead to better resource utilization without diminishing scientific quality, safety, or the protection of human subjects. Purpose In this study we modeled time-to-even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…We propose a framework based on a totally different approach that maps the administrative process through VSM, identifies barriers for trial opening through timing analysis and SNA, and examines system performance under different scenarios through DES. The use of systematic approaches to analyze the trial activation process, rather than case study alone, has been recognized as a key tool to make trials more efficient [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We propose a framework based on a totally different approach that maps the administrative process through VSM, identifies barriers for trial opening through timing analysis and SNA, and examines system performance under different scenarios through DES. The use of systematic approaches to analyze the trial activation process, rather than case study alone, has been recognized as a key tool to make trials more efficient [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…This sizable amount is exonerated if we consider that the administrative process associated with trial activation in academic medical settings includes up to 30 different activities, involves up to 11 participants, and lasts on average, from 44 to 172 days [ 6 , 8 , 17 , 18 ]. Such complexity translates into delayed trial activation, which affects patient enrollment goals [ 19 , 20 ] and diminishes the usefulness of trials by failing to attain evidence of investigated interventions on time [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Trials bureaucracy has been estimated at US$50,000 per site, 64 and the trial development process-from study conception to activation-can take upwards of 800 days in the United States 42 and 600 days in the United Kingdom. 43 Delays and associated costs also raised concerns that clinical research will be outpaced by the discoveries they are designed to test, 64,65 and one recent study estimated that 25% of industry trials recruit from lowincome countries to reduce costs. 66 Signs of diminished site capacity were found in Canada as a consequence of activation delays.…”
Section: Key Finding 1: Delays In Trial Activation Persist and Impactmentioning
confidence: 99%
“…31,[73][74][75] Moreover, because these collectives are inherently integrated, they may be well-positioned to consolidate infrastructure and improve patients' access to trials across communities. 22,75 It is worth noting, however, that networked groups are not de facto efficient entities, 42,65 are underfunded, 70 and have little, if any, control over their share of an institution's operating budget or the complex regulatory environment in which they function.…”
Section: Key Finding 4: Leveraging the Value Of Trials Networkmentioning
confidence: 99%
“…Using a site’s real-world data to analyze the size of the local patient population that satisfies a clinical trial’s eligibility criteria has been shown to accurately predict whether a trial could conceivably attain its accrual goals. 12 Prospectively eliminating studies that lack the required patient cohort size via a data-driven prescreening analysis would reduce the financial loss associated with unsuccessfully accruing trials. Enterprise research repositories, such as those that are built on the Informatics for Integrating Biology and the Bedside (i2b2) 13 platform, have been widely used in cohort identification for prospective studies, and those that have regular refreshes of clinical data can provide a reliable indication of prospective trial accrual.…”
Section: Introductionmentioning
confidence: 99%